The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1371/journal.pntd.0004780
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Point Mutations in the Voltage-Gated Sodium Channel from African Aedes aegypti Populations: Potential Phylogenetic Reasons for Gene Introgression

Abstract: BackgroundYellow fever is endemic in some countries in Africa, and Aedes aegpyti is one of the most important vectors implicated in the outbreak. The mapping of the nation-wide distribution and the detection of insecticide resistance of vector mosquitoes will provide the beneficial information for forecasting of dengue and yellow fever outbreaks and effective control measures.Methodology/Principal FindingsHigh resistance to DDT was observed in all mosquito colonies collected in Ghana. The resistance and the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
97
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(110 citation statements)
references
References 46 publications
8
97
2
3
Order By: Relevance
“…While the 1534C mutation is widespread, our study contributes to knowledge of the boundaries for each of the V1016 mutations, with the most westerly report of the 1016G mutation to date. Interestingly, the 1016I mutation has recently been detected in Ghana [27], alongside the F1534C substitution, suggesting a possible contact zone between the 1016G and 1016I mutations located between Saudi Arabia and West Africa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the 1534C mutation is widespread, our study contributes to knowledge of the boundaries for each of the V1016 mutations, with the most westerly report of the 1016G mutation to date. Interestingly, the 1016I mutation has recently been detected in Ghana [27], alongside the F1534C substitution, suggesting a possible contact zone between the 1016G and 1016I mutations located between Saudi Arabia and West Africa.…”
Section: Discussionmentioning
confidence: 99%
“…The vast majority of studies of resistance mechanisms in Ae. aegypti are from The Americas and Asia [19, 25, 26], though a recent first study from West Africa identified the presence of target site resistance shared with American populations [27]. Knowledge of resistance mechanisms in the Middle East and their relationship with other regions is currently lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, mutation V1016I was found, and often coexists with F1534C in South and North America, such as Venezuela [48], three French overseas territories [49], Brazil [50,51,52], Mexico [53], and the USA [54]. More recently, V1016I and F1534C were detected in Ghana, Africa [55], and a new mutation, T1520I, was found along with the F1534C mutation in a population in India [56]. …”
Section: Identification Of Single Nucleotide Polymorphisms (Snps) mentioning
confidence: 99%
“…More recently, V1016G, along with F1534C, was also detected in Ghana. Genomic sequence analysis suggests a possible migration event of mosquitoes carrying F1534C from South or North America to Africa [55]. …”
Section: Evolution Of Kdr Mutations In Aedes Aegyptimentioning
confidence: 99%
“…However, it is not clear if this variation reflects movement patterns of mosquitoes (genetic invasion) or ongoing mutation and selection. Evidence of resistance mutations spreading as mosquitoes move has been found in Ghana where mutation F1534C appeared, as a first record in Africa, associated with an intron phylogeny from Southeast Asia and South America (H. Kawada et al, 2016).…”
Section: Introductionmentioning
confidence: 99%